Education and moral respect for the medical student. Issue 1 (2nd January 2016) - Martin, Christopher
Abstract: In this paper I argue that medical education must remain attuned to the interests that physicians have in their own self-development despite ongoing calls for ethics education aimed at ensuring physicians maintain focus on the interests of the patient and society. In particular, I argue that medical education should advance (and abide by) criteria defining what counts as an educationally worthwhile activity from the perspective of the medical student understood as a learner. I offer a preliminary account and justification of such criteria, arguing that such criteria warrant a process of ethical formation that better serves the interests of medical students, their patients and society.